AI sebagai Tutor Cerdas bagi Guru Pemula pada Kegiatan Program Induksi - Badriah Badriah (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
This study presents a review of research and manuscripts that discuss the utilization of Artificial Intelligence (AI) applications for novice teachers participating in induction programs during their early years of teaching. The study employs a qualitative method, gathering data from journal manuscripts and browser publications focused on the pedagogical use of AI. The collected data is categorized to address research questions related to the benefits of AI for novice teachers and the challenges they face when using AI for teaching. The analysis results indicate that for novice teachers, AI provides opportunities to serve as a tutor or assistant that can be used anytime, anywhere, according to the novice teachers' availability and ability to manage learning, teaching, and assessment. Additionally, AI can serve as a resource to enhance pedagogical knowledge and understanding, automate lesson planning and scheduling, provide teaching feedback, and facilitate learning assessments. The challenges faced by novice teachers revolve around their ability to decide how and when to appropriately use AI-based tools or applications.